2019
DOI: 10.1007/s10886-019-01082-4
|View full text |Cite
|
Sign up to set email alerts
|

Common Cerambycid Pheromone Components as Attractants for Longhorn Beetles (Cerambycidae) Breeding in Ephemeral Oak Substrates in Northern Europe

Abstract: Longhorn beetles are ecologically important insects in forest ecosystems as decomposers of woody substrates, microhabitat engineers, and as components of forest food webs. These species can be greatly affected both positively and negatively by modern forestry management practices, and should be monitored accordingly. Through headspace sampling, coupled gas chromatography-electroantennography, gas chromatography-mass spectrometry, and field bioassays, we identified two compounds, 2-methyl-1-butanol and 3-hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
(39 reference statements)
4
6
0
Order By: Relevance
“…Phymatodes testaceus was attracted to K6 + K8 + ethanol in our study and its attraction to K6 has been shown in previous studies (Hanks & Millar, 2013;Sweeney et al, 2014;Molander et al, 2019b). The aggregation sex pheromone of P. testaceus is (R)-2-methylbutan-1-ol (Hanks et al, 2019), so attraction of the species to K6 or K6 + K8 + ethanol suggests it is using pheromones of heterospecifics, combined with cues of stressed hosts (ethanol) as kairomones to locate mutually suitable larval hosts (Hanks et al, 2007;Molander et al, 2019b).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Phymatodes testaceus was attracted to K6 + K8 + ethanol in our study and its attraction to K6 has been shown in previous studies (Hanks & Millar, 2013;Sweeney et al, 2014;Molander et al, 2019b). The aggregation sex pheromone of P. testaceus is (R)-2-methylbutan-1-ol (Hanks et al, 2019), so attraction of the species to K6 or K6 + K8 + ethanol suggests it is using pheromones of heterospecifics, combined with cues of stressed hosts (ethanol) as kairomones to locate mutually suitable larval hosts (Hanks et al, 2007;Molander et al, 2019b).…”
Section: Discussionsupporting
confidence: 74%
“…Clytus arietis was attracted to K8, confirming the likely role of hydroxyoctanones as aggregation pheromones (Schröder, 1996). Molander et al (2019b) showed that P. detritus males emitted (R)-3-hydroxy-2-hexanone and lesser amounts of (S)-2-hydroxy-3-octanone and that both sexes were attracted to a 5 : 1 blend of racemic 3-hydroxy-2-hexanone (i.e., K6) and racemic 2-hydroxy-3-octanone, but not to either compound by itself. Our results, showing that P. detritus was attracted only to lure combinations that included both K6 and K8 (racemic 3-hydroxy-2-octanone), confirm that both the 6-and 8-carbon hydroxyketones are necessary for attraction of P. detritus, and suggest the relative position of the hydroxyl-and carbonyl-functional groups (i.e., 2,3 vs. 3,2) on the hydroxyoctanone may be less critical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, in the current study, four species were caught in good numbers which had not been caught at all in the 2010 study, potentially suggesting that the pheromones of these species may consist of two or more components of the tested blend that act synergistically, with minimal attraction to the individual components. This synergism of multiple pheromone components has been observed with cerambycid species in several trapping studies [ 50 , 51 , 52 , 53 ]. A second factor that may have contributed to the difference in the mix of species caught between the two studies was the timing of deployment of the experiments.…”
Section: Discussionsupporting
confidence: 60%
“…To date, attractants, including those identified as pheromones, have been identified for more than 115 cerambycid species (reviewed by and have been used to develop synthetic volatile pheromone lures based on the conservation of a number of pheromone structural motifs within and among cerambycid genera, tribes, and subfamilies. This pheromone parsimony has contributed to the effectiveness of these lures and to their value as a tool for testing attraction of cerambycids to pheromone components, community analysis, and monitoring for invasive species and for rare or endangered species (Ray et al 2014;Larsson 2016;Fan et al 2019;Molander et al 2019;Rassati et al 2020). A number of novel pheromone structures within the Cerambycidae have recently been identified for a number of species and genera, increasing the structural diversity known for this family (Ray et al 2011(Ray et al , 2012bDiesel et al 2017;Millar et al , 2019Mitchell et al 2018;Meier et al 2019).…”
Section: Introductionmentioning
confidence: 99%